(untitled) (Journal of Asian Development Studies, 2024)
The intertwining of economics and foreign policy has become increasingly evident in the modern geopolitical landscape, with the US-China trade war as a prominent case study. This critical abstract examines the significance of economic considerations in shaping foreign policy decisions, particularly in the context of the US-China trade war, through the lens of political economy. The US-China trade war, initiated in 2018, symbolizes the complex interplay between economic interests and political objectives. At its core, the conflict represents a strategic maneuver by the United States to address longstanding grievances regarding trade imbalances, intellectual property theft, and market access restrictions. Conversely, China’s response reflects its aspiration to assert itself as a global economic powerhouse and safeguard its developmental model against external pressures. Through a political economy perspective, this abstract delves into the multifaceted dynamics driving the US-China trade war. Economic theories, such as mercantilism and comparative advantage, offer insights into the motivations behind both nations’ protectionist measures and tariff escalations.Moreover, the abstract evaluates the efficacy of economic coercion as a foreign policy tool and its implications for international relations. While tariffs and trade barriers can pressure adversaries, they also entail risks, such as retaliatory measures, economic volatility, and unintended consequences. Additionally, the abstract examines the role of domestic politics and interest groups in shaping the trajectory of the trade war, highlighting the interplay between economic nationalism, electoral dynamics, and policy formulation